Teaching New Technologies and Life-Long Learning Skills: A Sample Approach and Its Evaluation - Class, Christina B (International Journal of Advanced Corporate Learning (iJAC), 2011)
Christina. B. Class studied Business Informatics at the University of Mannheim, Germany, and made her PhD in the Computer Engineering and Networks Laboratory at the Swiss Federal Institute of Technology in Zurich, Switzerland. From 1999 to 2008 she was professor for computer science at the Lucerne University of Applied Sciences and Arts in Switzerland. In 2008 she joined the computer science department at German Jordanian University in Amman, Jordan. Dr. Class has several certificates and degrees in computer science didactics. (Christina.Class@gju.edu.jo)